Justice for profit? The transfer of claims or assignment model - Herrero Suárez, Carmen (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The exercise of an individual claim for compensation may be ineffective in certain scenarios, such as in the case of massive and dispersed damages arising from a single conduct. To address its limitations, various solutions are being developed in practice, both procedural and substantive. The objective of this paper is to examine one of these solutions: the contractual assignment of compensation rights to a professional claimant or litigation vehicle, assessing its admissibility and implementation within the European framework, as well as the role it plays or could play in the future in resolving problems of access to justice for victims of anticompetitive practices or other unlawful conduct.
Keywords: Access to justice; class actions; assignment model; litigation funding